Microbiological colourants removal from sugar beet molasses vinasse: The effects of process parameters and vinasse dilution - Marta Wilk; Małgorzata Krzywonos; Przemysław Seruga (Economic and Environmental Studies (E&ES), 2017)
Distilleries, in addition to ethanol, produced vinasse which is hazardous for the environment. Sugar beet molasses vinasse (BMV) is the most problematic waste from distilleries because of the coloured compounds contained therein. Traditional methods of the removal of the pollutant load from the waste do not allow simultaneous decolourization. The paper presents a microbiological method of coloured compounds removal from BMV. The conditions of the process (pH and temperature) and vinasse concentration were optimized. The bacteria Lactobacillus plantarum MiLAB393 applied showed the decolourization activity of 26% in medium consisted of 30% v/v of BMV at pH0=6.5 and 35.8êC.
Keywords: Q16; Q53; Q57; 330; decolourization; sugar beet molasses vinasse; Lactobacillus plantarum; lactic acid bacteria